The prevalence and determinants of social anxiety disorder among people living with HIV/AIDS in Southwestern Ethiopia: a cross-sectional study - Alemayehu, Yadeta; Adem Hussen, Mustefa; Abdu, Zakir; Dule, Aman; Hajure, Mohammedamin; Mulatu, Gebremeskel; Gezimu, Wubishet; Alemu, Solomon Seyife; Wedajo, Lema Fikadu (Frontiers in Psychiatry, 2024)
Background Social anxiety disorder imposes impacts of functional disability, poor educational achievement, loss of work productivity, social impairment, greater financial dependency, and impairment in quality of life. Therefore, the aim of this study was to assess the prevalence and identify determinants of social anxiety disorder among people living with HIV/AIDS. Methods A cross-sectional study was conducted from 1 to 30 May 2022 among 354 people living with HIV using a simple random sampling technique. The Social Phobia Inventory (SPIN) Scale was used to assess the presence of social anxiety disorder. Data were gathered using chart review tools and a structured questionnaire, which was administered by a pretested face-to-face interviewer. SPSS version 25 was used to analyse the data once they were imported into EpiData Manager version 4.6. Binary and multivariable logistic regressions were performed. After calculating odds ratios with a 95% confidence interval (CI), statistical significance was established at p < 0.05. Results A total of 336 respondents participated in the study, resulting in a response rate of 94.91%. The magnitude of social anxiety disorder was 32.44% (95% CI: 27.4, 37.2). Being female [adjusted odds ratio (AOR) = 3.55, 95% CI: 1.61, 7.84], having a stage III/IV HIV/AIDS status (AOR = 3.17, 95% CI: 1.10, 9.13), being alcohol dependent (AOR = 2.81, 95% CI: 1.45, 5.44), and having perceived stigma (AOR = 5.62, 95% CI: 2.95, 10.72) were predictors of social anxiety disorder. Conclusion In this study, approximately one-third of people living with HIV/AIDS had social anxiety disorder. Being female, having a stage III/IV HIV/AIDS status, being alcohol dependent, and having perceived stigma were predictors of social anxiety disorder. Therefore, training for health care providers on the screening, counselling, and management of social anxiety disorder is important.